Gerenciamento de resíduos sólidos industriais: um estudo para a área mineira da Bacia do Médio São Francisco - Guilherme Augusto Guimaraes Oliveira (2005)
The increasing concern with environmental questions has forced the public managers to take a position about the impacts caused by the productive activities. One of the main negative impacts generated by the industrial and mining enterprises happens due to inadequate disposal of its solid waste. This work contributes in the evaluation of the generation and destination of waste, created by the industrial and mining enterprises installed in the area of the basin of the medium San Francisco, and in the verification of the level of available information on this aspect in the agency of ambient control of the State. For this, it was carried through an ample survey of data about generation and disposal of solid waste for the enterprises installed in the mining area of the basin of the medium San Francisco. 96 enterprises, distributed in 26 of the 86 cities that compose the region had been identified. In the processes of licensing and the programs of ambient self monitoring of these enterprises, data of generation and destination of solid waste had been collected. In accordance to the information in the processes of the FEAM, 294,224.58 tons of residues are generated per year, and the recycling is the most used destination for these residues, corresponding to 52,5%. Its important to highlight that the generation of dangerous solid waste is few relevant (120,78 tons per year). Later, sectors representative enterprises had been chosen and questionnaires had been applied, aiming the detailing of the information obtained in the system. When comparing these data with the results of the State Inventory of Industrial Solid Waste, it is verified that the other industrial activities would have to participate of the survey. The analysis of the information demonstrates that the management of solid waste in the region had advance among licensed enterprises, fact that validates its use as an environmental control. Meanwhile, it demonstrated that the cities continue to neglect the legal mandatory to manage the solid waste, even though the significant generation of industrial solid waste in the region and already resemble the amount of domestic solid waste generated. The accomplishment of periodic surveys for the evaluation of the management of the industrial waste and the implementation of a program of integrated management of solid waste becomes necessary, including the mining and industrial solid waste.